Modernidade e revolução social: uma digressão sobre os significados da imanência e da transculturação nas sociedades modernas e contemporâneas - Luís Antonio Groppo (Ciências Sociais Unisinos, 2007)
Through a bibliographic review, the article discusses the notions of modernity and modernization. It highlights the configuration of both notions in the bourgeois revolutions and considers the present moment, the global era, as a new acceleration of processes of socio-economic modernization, rather than a breaking of paradigms that would lead us to post-modernity. However, a reflection about some notions proposed by critical thinkers who at some point identified with post-modernism must be done in order to better understand both moments of modernity the present one and the moment of the bourgeois revolutions. These are the notions of emancipation according to Boaventura Sousa Santos and of immanence according to Michael Hardt and Antonio Negri. This reflection is done here and is supplemented by a reflection about the concept of transculturation. In this way a more plural and complex view of modernity can be constructed